A reflection on the impact of COVID-19 on primary care in the United Kingdom. Issue 5 (2nd September 2020) - Gray, Richard; Sanders, Chris
ABSTRACT: The COVID-19 pandemic has presented both challenges and opportunities for those working in health and social care in the United Kingdom (UK). With much focus on secondary and acute care at this time, there has been less communication and understanding about the impact on primary care. This discussion paper is based on the experience of one of the authors working as a general practitioner/family doctor during the pandemic and rapid changes are described during this time (April 2020). Two important themes emerged from this experience focusing on the importance of supporting one another and new roles and ways of working. It can be argued that the challenges presented by COVID-19 have expedited positive and potentially sustainable change in UK primary care that has been needed for some time. The authors discuss the implications for future working and make a series of recommendations for primary care relating to the importance of supporting the workforce, remote consultations and communication, regular team meetings, and development of integrated care. It is suggested that many of the challenges highlighted can be addressed by placing a greater emphasis on the use of interprofessional education (IPE) to underpin and support effective collaborative working.